(untitled) (Current Horticulture, 2024)
An experiment was conducted to find out photosynthetic efficiency of elephant-foot yam (Amorphophallus paeonifolius Dennst.) at CTCRI, Thiruvananthapuram, during April-August 2017. In the search of photosynthetically efficient climate smart crops/varieties, net photosynthetic rate (Pn), stomatal conductance (gs) and intercellular CO2 (Ci) were studied in three contrasting elephant-foot yam genotypes, viz. Sree Padma, Gajendra and Idukki local under ambient (400 ppm) and eCO2 (eCO2) (600, 800 and 1000 ppm) and Pn at photosynthetic photon flux densities (PPFDs), viz. 200, 400, 600, 800, 1000, 1200 and 1500 µmol/m2/h at 30°C and 400 ppm CO2 using portable photosynthesis system LI-6400, LICOR, USA. The maximum Pn of three genotypes was recorded at PPFD of 1500 µmol/m2/s. The Pn steadily increased due to short-term (ten minutes) exposure at eCO2 concentrations between 400 ppm and 1000 ppm in all genotypes. The genotypes had average Pn of 17.97, 25.07, 29.44 and 30.06 µmol CO2/m2/s at 400, 600, 800 and 1000 ppm CO2 respectively. All of them had 56.71-82.51% hike in Pn at eCO2 (1000 ppm) compared to ambient CO2 (400 ppm). However, per cent of increment in Pn at eCO2 for every 200 ppm between 400 and 1000 ppm significantly declined (-4.81-9.03%) at 1000 ppm CO2. The differences in Pn were statistically significant across all genotypes (P>0.05) and CO2 concentration (P>0.001). However, interaction effect of genotypes and CO2 concentrations on Pn was insignificant, whereas Pn had a quadratic relation with increase in CO2 concentration (R2= 0.932). The gs in all genotypes increased at 600/800 ppm eCO2 concentrations but declined at 1000 ppm CO2 compared to 400 ppm. All genotypes had average gs of 0.394 0.480, 0.491, 0.280 mol H2O/m2/s at 400, 600, 800 and 1000 ppm CO2 respectively. However, per cent of increment in Ci at eCO2 for every 200 ppm between 400-1000 ppm significantly declined (-36.40- -40.04%) at 1000 ppm CO2. The differences in gs were statistically significant across elephant foot yam genotypes (P>0.05) and CO2 concentrations (P>0.01). However, the interaction effect of genotypes and CO2 concentration on gs is insignificant. The three elephant foot yam genotypes had the average Ci of 319.33, 487.07, 655.73 and 815.24 µmol CO2/mol air at 400, 600, 800 and 1000 ppm CO2 respectively. However, the per cent of increment in Ci at eCO2 for every 200 ppm between 400-1000 ppm significantly declined (22.46-27.38%) at 1000 ppm CO2. The differences in Ci were statistically significant across genotypes and CO2 concentrations (P>0.001). However, the interaction effect of genotypes and CO2 concentrations on Ci was insignificant. Statistically the net photosynthetic rate had a quadratic relation with the Ci (R2= 0.710). The differences in total chlorophyll and protein content in the leaves of three elephant foot yam genotypes were statistically significant. Nevertheless, the gas exchange parameters were not influenced by the total chlorophyll and protein content.